2020
DOI: 10.3102/0034654320922140
|View full text |Cite
|
Sign up to set email alerts
|

Do Book Giveaway Programs Promote the Home Literacy Environment and Children’s Literacy-Related Behavior and Skills?

Abstract: Book giveaway programs provide free books to families with infants to encourage caregivers to begin reading to their children during infancy. This meta-analysis of 44 studies retrieved from 43 articles tests the effects of three major book giveaway programs: Bookstart (n = 11), Reach Out and Read (n = 18), and Imagination Library (n = 15). Effect sizes were aggregated within two domains—home literacy environment and literacy-related behavior and skills—before being averaged across studies. The findings corrobo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 61 publications
0
22
0
1
Order By: Relevance
“…Although in the current set of studies enhancements did not outweigh adult guidance, future studies should further explore whether a sensible system of digital storytelling techniques may be powerful enhancements of picture book apps that outweigh or complement adult guidance. Fourth, in the studies that we meta-analyzed, only a few authors included reading motivation as an outcome measure, even though we may expect that interest in reading is one of the main outcomes of book reading (e.g., De Bondt et al, 2020). Last, most studies involved children in the age range of 4 to 5 years, making it hard to generalize the current findings to infants or the older children who are at the transition from emergent to conventional readers.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the current set of studies enhancements did not outweigh adult guidance, future studies should further explore whether a sensible system of digital storytelling techniques may be powerful enhancements of picture book apps that outweigh or complement adult guidance. Fourth, in the studies that we meta-analyzed, only a few authors included reading motivation as an outcome measure, even though we may expect that interest in reading is one of the main outcomes of book reading (e.g., De Bondt et al, 2020). Last, most studies involved children in the age range of 4 to 5 years, making it hard to generalize the current findings to infants or the older children who are at the transition from emergent to conventional readers.…”
Section: Discussionmentioning
confidence: 99%
“…Just like word reading, orthographic knowledge appears to be script dependent. Cross-language effects of orthographic knowledge on reading have been reported in bilingual students whose two languages are based on the Roman alphabet, such as Spanish-English bilinguals and English-French bilinguals (Deacon, Commissaire, Chen, & Pasquarella, 2013;Deacon, Wade-Woolley, & Kirby, 2009). In contrast, cross-linguistic relations have not been observed in bilingual students whose two languages are represented by different scripts, such as Chinese-English bilinguals (e.g., Wang, Perfetti, & Liu, 2005), Korean-English bilinguals (e.g., Wang, Park, & Lee, 2006), and Persian-English bilinguals (Arab-Moghaddam & Sénéchal, 2001).…”
Section: Word-reading Skills Orthographic Knowledge and Scriptsmentioning
confidence: 99%
“…Home–school supports, such as home literacy environments, provide families with a way of enhancing learning experiences in the L1 or L2 (Alexander, Entwisle & Olson, 2001; Auerbach, 2006; Castro, Páez, Dickinson, & Frede, 2011; Davies, Aurini, & Milne, 2020; de Bondt, Willenberg, & Bus, 2020; Dong, Wu, Dong, & Tang, 2020; Hammer, Miccio, & Wagstaff, 2003). For example, maternal book reading and teaching practices were related to children’s oral language skills and knowledge of concepts about print, respectively, in middle‐class families in India whose children were enrolled in English kindergartens (Kalia & Reese, 2009).…”
Section: Societal/contextual Factors Related To L1 and L2 Word Readingmentioning
confidence: 99%
“…24 It has been shown that DPIL participants experience increased frequency of reading at home, greater family engagement and interest around books, and a home literacy environment enhanced by the significant number of books delivered. [25][26][27][28] DPIL participants also show evidence of improved skills directly related to kindergarten readiness, namely letter identification, phonologic awareness, and letter naming fluency. [29][30][31] Finally, an urban school district found that DPIL participants scored better on the language and math sections of its validated kindergarten readiness indicator than nonparticipants.…”
mentioning
confidence: 99%